Islamic education and interfaith tolerance - Febriana, Lety; Syubli , Syubli; Firmasari, Desi; Nuryana, Nana (Universitas Ahmad Dahlan, 2025)
This study aims to examine the contribution of Islamic education in fostering interfaith tolerance in multicultural rural communities, with a focus on Surobali Village, Kepahiang Regency, Bengkulu. The challenge of interfaith tolerance in rural communities arises because the implementation of Islamic education has not been fully effective in shaping awareness and tolerant attitudes, even though Islam teaches the principle of rahmatan lil 'alamin. The research gap lies in the lack of field studies highlighting contextual Islamic education practices in fostering social harmony. Using a qualitative approach through observation, interviews with religious leaders, educators, community members, and documentation of social-religious activities, this study found that integrative Islamic education that combines Islamic values with local wisdom such as cooperation, consultation, and mutual respect is able to create spaces for dialogue, strengthen interfaith interactions, and foster inclusive attitudes. These findings have implications for educators to design more moderate and contextual learning, for policymakers to support tolerance-based education programs, for religious leaders to strengthen inclusive preaching, and for future researchers to explore other dimensions such as economics and technology in building social cohesion. Overall, transformative Islamic education has proven to be a strategic foundation for strengthening tolerance and has the potential to guide educational policies toward a more inclusive and sustainable paradigm.